Misfit forms : paths not taken by the British novel - Nandrea, Lorri G. (Fordham University Press, 2015)
'Misfit Forms' re-interprets a series of choices that shaped the development of the British novel. Histories of the novel often situate the early nineteenth century as a culminating moment in the novel's 'rise'. However, a look at the complicated junctions negotiated by the novel during the eighteenth century reveals not only achievements but also exclusions - paths less travelled. Pairing readings of novels by Defoe, Sterne, Gaskell, Hardy, and Charlotte Brontë with less familiar texts, including printer's manuals and grammar treatises, each chapter brings out an occluded mode.